We Need Action on Social Determinants of Health - but Do We Want It, too? Comment on "Understanding the Role of Public Administration in Implementing Action on the Social Determinants of Health and Health Inequities" - Evelyne de Leeuw (Kerman University of Medical Sciences, 2016)
Recently a number of calls have been made to mobilise the arsenal of political science insights to investigate - and point to improvements in - the social determinants of health (SDH), and health equity. Recently, in this journal, such a rallying appeal was made for the field of public administration. This commentary argues that, although scholarly potential should justifiably be redirected to resolve these critical issues for humanity, a key ingredient in taking action may have been neglected. This factor is 'community.' Community health has been a standard element of the public health and health promotion, even political, repertoire for decades now. But this commentary claims that communities are insufficiently charged, equipped or appreciated to play the role that scholarship attributes (or occasionally avoids to identify) to them. Community is too important to not fully engage and understand. Rhetorical tools and inquiries can support their quintessential role.